Pengaruh Latihan Ketrampilan Sosial terhadap Kemampuan Sosialisasi pada Lansia dengan Kesepian Di Panti Wredha Semarang - Masithoh, Anny Rosiana; Hamid, Achir Yani S.; Sabri, Luknis (Jurusan Keperawatan FIKES UNSOED, 2012)
The inability to socialize in an environment that is different from the previous life is a significant stressor for the elderly. The aim of this research was to analyze the correlation between social skill training and socialization ability of eldery with loneliness in nursing home. This research used quasi experimental pre-post test with control group design. The research took place at nursing homeÃ¢â‚¬ÂAÃ¢â‚¬Â for intervention group with 27 subjek and nursing home Ã¢â‚¬Å“BÃ¢â‚¬Â for control group with 28 subjek. The result showed a significant difference of elderly socialzation ability before and after that there was training with social skill training. It is proved by an increase of social ability of eldery in intervention group. This research recommended that social skill training needs to be given in elderly with loneliness